Expression and Promoter Analysis of Six Heat Stress-Inducible Genes in Rice - Wirat Rerksiri; Xianwen Zhang; Hairong Xiong; Xinbo Chen (The Scientific World Journal)
During the long evolutionary process, plant gradually formed a series of strategies and mechanisms to cope with stress environment such as drought, heat, cold, and high salinity. Six highly heat responsive genes were identified in rice by microarray data analysis. The qRT-PCR analysis confirmed that the expression of these six genes were highly heat inducible and moderately responded to salt stress, polyethylene glycol, and abscisic acid treatment, but little affected by cold treatment. Promoters of the three highly heat-inducible genes (OsHsfB2cp, PM19p, and Hsp90p) were used to drive GUS gene expression in rice. The results of the GUS gene expression, histochemical staining, and GUS activities in panicles and flag leaves of the transgenic rice plants confirmed high heat-induced GUS activities and moderate drought-induced activities. The three promoters exhibited similar high activity lever in rice leaf under heat, but OsHsfB2cp and PM19p showed much higher activities in panicles under heat stress. Our work confirmed that the OsHsfB2c and PM19 promoters were highly heat inducible and further characterization and reconstruction of cis-elements in their promoters could lead to the development of highly effective heat-inducible promoters for plant genetic engineering.